Agricultura de precisão - aplicada a fertilidade do solo para produção de sementes de arroz irrigado (Oryza sativa L.) - Leite, Claudio Wrege (2007)
This paper resulted from the analysis of three harvests in a row of the following crops: 2003/2004 rice harvest; 2004/2005 soybeans harvest; 2005/2006 rice harvest, as well as the 2005/2006 post-harvest rice crop (Oryza sativa L.) on Granja do Salso (Salso Farm) in Sta. Vitória do Palmar county, R.S. with the purpose of applying precision agriculture to soil fertility in the production of irrigated rice seeds. A 22,18ha area was used, which was subsequently divided into 15 1,48ha lots with fixed meshes of 122m x 122m (grid). Soil analyses were performed before each sowing and also after the last year s rice harvest for each lot. Soil sampling was obtained by collecting 9 subsamples which made up the composite sample; these samples were then sent to the Soil Analysis Laboratory at UFPel. Georeferral of soil sampling was measured from each lot center. A yield map was established and fertility maps were created both from soil analyses and seed physiological quality determination: Management areas with differentiated fertilization to correct and make phosphorus and potassium contents uniform were established. The results obtained show that: precision agriculture provided an increase in soil fertility by the use of management areas; the use of management areas decreased soil fertility variability among the lots of the area under analysis; no correlation between soil fertility and irrigated rice crop yield was found; no correlation between soil fertility and seed physiological quality in irrigated rice was found.